Analisis Sociological Jurisprudence Putusan Hakim Pada Tindak Pidana Perzinahan (Overspell) Dalam Kaitannya Dengan Perkawinan Dibawah Tangan (Studi Putusan Pengadilan Negeri Marisa Nomor 98/Pid.B/2020/Pn Mar Jo. Nomor 99/Pid.B/2020/Pn Mar) - Bestian, Seftra; Amu, Robby W.; Kasim, Ramdhan (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to find out the court's decision on the crime of adultery associated with underage marriage at the Marisa District Court of Pohuwato Regency in case decision Number 98/Pid.B/2020/PN Mar Jo. Number 99/Pid.B/2020/PN Mar and To Know and analyze the legal considerations of the Marisa Court Judges in case decision Number 98/Pid.B/2020/PN Mar Jo. Number 99/Pid.B/2020/PN Mar and what obstacles were faced in making a decision in case number 98/Pid.B/2020/PN Mar Jo. Number 99/Pid.B/2020/PN Mar on the criminal offense of adultery (Overspell) of underage marriage. The implementation of this research is empris research. In this study, researchers used a qualitative method. The author uses research that is descriptive analytical Sociological, according to Suharsimi Arikunto descriptive analytical is research intended to collect information about the status of existing symptoms, namely symptoms of the situation as it is at the time the research is conducted. In the decision on the criminal case of adultery associated with underage marriage, the judge has carried out the decision in accordance with the applicable positive legal regulations, seeing several considerations of the judge according to the defendant's statement, evidence of instructions. Based on the applicable positive law when associated with religious law, this underhand marriage is declared valid. However, in terms of the judge's decision, it has taken into account the principle of justice. In addition, the perpetrator of this crime is legally guilty, but the judges imposed the sentence by looking at the defendant's mitigating and aggravating statements. Complex legal considerations are an important part of the process of judges handing down decisions in adultery cases, especially in the context of underage marriage. Judges must consider various legal, ethical, and cultural factors in making fair and balanced decisions.